Immobilization of proteases with a water soluble–insoluble reversible polymer for treatment of wool - Silva, Carla J. S. M. (2006)
A commercial protease, Esperase, was covalently linked to Eudragit S-100, a reversible soluble–insoluble polymer by carbodiimide coupling. When compared to the native enzyme, the immobilized form presented a lower specific activity towards high molecular weight substrates but a higher thermal stability at all temperatures tested. The optimum pH of the immobilized protease was shifted towards the alkaline side by about one pH unit while there was no change in optimum temperature between the free and immobilized protease. The immobilized protease exhibited a good storage stability and re-usability. Enzymatic treatment of wool using proteases has been investigated for wool shrink-resist finishing. It was found that using the immobilized protease in the enzymatic treatment of wool there was a reduction of weight and fibre tensile strength loss because the proteolytic attack is only limited to the cuticle surfaces of wool fibres. This novel approach is a promising alternative for wool shrink-resist finishing to replace the conventional chlorine treatments. This environmentally friendly bioprocess needs to be further characterized to a complete understanding and optimization.